Development of Knowledge Management Model to Improve the Performance of Employees in Small Hotels, Greater Mekong Sub Region Tourism Development Area - Wicheanwan, Penpaksina; Kansarnsanti, Varistha; Sribusdi, Piyada (Journal of Humanities and Social Sciences Thonburi University, 2022)
This research primarily aimed to: 1. Study the guidelines for promoting the performance; 2. Develop knowledge management to promote the performance; and 3. Propose guidelines for developing a model of knowledge management to promote the performance of employees in small hotels. This study was conducted using mixed methods approach including: 1. Quantitative research is conducted by using questionnaires for the tourists and employees. The analyzing the data by mean, standard deviation. 2. Qualitative data were collected by in-depth interviews and focus group for executives/staff of hotels, travel agent, guide, the provincial tourism office in the area, research academics, and using content analysis. It was found that 1. Knowledge acquisition in operation has been adjusted to the future of work after COVID-19 pandemic. 2. Knowledge creation by using more technology. 3. Knowledge transfer and utilization to be connected with business groups that can link services/operation as well as further business development to meet the needs of different and diverse tourists. 4. Knowledge storage and retrieval for training the knowledge skills upskill/ reskill/ newskill to support after crisis the COVID-19 pandemic.